The Effect of Profitability on Firm Value Moderated by Dividend Policy (Empirical Study of IDX High Dividend Companies 20 Years 2019-2021) - Utari Setia Pratiwi; Hadi Pramono; Novi Dirgantari; Slamet Eko Budi Santoso (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to examine the effect of Profitability on Firm Value with Dividend Policy as a Moderating Variable in 20 High Dividend Companies listed on the Indonesia Stock Exchange in 2019-2021. The method used for sampling in this research is by using a purposive sampling technique, obtained as many as 19 data that meet the sample criteria. The data analysis method used in this research is Moderated Regression Analysis. The results of this research prove that Profitability has no effect on Firm Value. However, the Dividend Policy variable can moderate in this case strengthening the influence of Profitability on Firm Value.